Some reflections on a global strategic culture issue - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2019)
Drawing on the works of leading European and Russian scientists and scholars of the XX-XXI centuries, on the results of many international and national research projects as well as on my own investigations in such interdisciplinary realm as social ecology of the large cities of the world and social ecology in the digital age, I came to the following conclusions. The global strategic culture is a product of the New Times when the people began to realize that our planet is spherical not only as a natural organism but a social one as well. It meant that Europe as social organism has a space for its further expansion and enrichment into the virgin lands. The reverse side of the same coin has been confirmed by of atomic nucleus fission that showed the principled relativity of such notion as a ‘big’ and ‘small.’ A key role in the shaping of a global strategic culture has been played by scientific and technological progress on the edge of the XX and XXI centuries, technologically developed and tested between and just after the WWI and WWII and confirmed by the testing of nuclear arms in the mid1940s. The essence of my concept of global strategic culture is its all-embracing and all-penetrating character coupled with a permanently speeding up its time-space parameters. I interpret the global strategic culture as a mean of survival of humanity together with his living environment and consider these features as the key distinguishing features of this cultural archetype. These features differs this archetype from all other cultural archetypes that have been characterized by a small set of very stable (unchangeable) signs.